Makna Konotatif dalam Puisi Bahasa Sunda yang Berjudul â€œDoâ€™a Pikeun Guruâ€ Karya Kustian - Kurniasih, Kurniasih; Nunuy Nurjanah, Nunuy Nurjanah; Isnendes, Retty; Firdaus, Winci (ppjbsip, 2023)
Poetry is an artistic expression that uses words creatively and rhythmically. It is a way to convey feelings, thoughts, or experiences through specially selected language to create an aesthetic impression, rhythm, and beauty. Poetry can be an expression of deep feelings, a picture of nature, a narrative about life, or simply a reflection of various aspects of life. The purpose of this study was to determine the connotative meaning in Sundanese poetry entitled Do'a Untuk Guru by Kustian. The method in this study is a qualitative method, with data collection through reading, understanding, and translating. The result of this study is 1 type of associative meaning found in the poem entitled